Pengaruh Pupuk Vermikompos dan NPK terhadap Pertumbuhan dan Hasil Kedelai Edamame pada Tanah Podsolik Merah Kuning - Reski, Silvanus; Susana, Rini; Ramadhan, Tris Haris (Fakultas Pertanian Universitas Tanjungpura, 2024)
Edamame soybeans (Glycine max (L) Merill) are a type of soybean plant that can be consumed and can be harvested fresh. The development of soybean commodities in West Kalimantan still faces a number of challenges, one of which is low productivity. The use of soil as a planting medium for edamame soybeans is faced with various problems, including poor soil physical and chemical properties. Providing vermicompost organic fertilizer can cause the solid soil to become crumbly, increase its porosity, improve soil aeration and drainage and can cause the pores to open and soil aeration and NPP to supplement the nutrient needs that are lacking in the soil. This research aims to obtain the dose of vermicompost fertilizer, the dose of NPP and the best dose of the interaction of vermicompost fertilizer and NPP on the growth and yield of edamame soybeans on RYP soil. The research was carried out on land located in Southeast Pontianak District, Pontianak City. The research was carried out from August